Cymbiodyta lishizheni sp. nov., the second species of the genus from China - Jia, Fenglong; Lin, Renchao (Zootaxa, 2015)
The water scavenger beetle genus Cymbiodyta Bedel contains 30 species (Jia & Short 2010, Short & Fikáček 2011), most of which are distributed in North America. Only one species (Cymbiodyta orientalis Jia & Short, 2010) has been described since the worldwide revision of the genus by Smetana (1974). This taxon was the second species of the genus known from the Old World and the first species known from the Oriental Region. Subsequently, Jia (2014) described the male of C. orientalis Jia & Short and provided photographs of the aedeagus.